The Uses of the Medieval Past in Contemporary European Political Discourse: Some Reflections Arising from the Portuguese Case - Miguélez,Alicia (2023)
Abstract References to the past have always been a common trope in political discourse. Either alluding to more recent or distant periods, processes, events, figures, or works, political actors and groups often use the past to convey certain ideas or aspects of their own agenda. This article examines the uses of the Middle Ages in twenty-first-century political discourse, using Portugal as a starting point within a broader European context. We delve into several explicit and implicit verbal and non-verbal references to the medieval past made by local, regional, and national political agents and groups. Three questions guide our research: 1) Are criteria of truthfulness and correctness relevant for this type of discourse? 2) Is it effective? 3) What are the differences between political ideologies when it comes to using the Middle Ages? We argue that the instrumentalization of the medieval past goes far beyond ideology itself, and that its value resides more in its political effectiveness than in the veracity of the claims and the intentionality or awareness of the agents that use this rhetorical device.